2012
DOI: 10.5152/tdd.2012.02
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Intermittent Isotretinoin Therapy in Moderate Acne Vulgaris

Abstract: Amaç: Bu çalışmada orta şiddetli akne olgularında, aralıklı düşük doz izotretinoin tedavisinin etkinlik, yan etki, yaşam kalitesine etkileri ve nüks görülme sıklığının araştırılması amaçlanmıştır. Gereç ve Yöntemler: Eylül 2007-Nisan 2009 tarihleri arasında akne polikliniğimizde izlenen hastalar retrospektif olarak incelendi. Haftada üç gün 20 mg/gün sabit dozda izotretinoin uygulanan hastalar değerlendirmeye alındı. Olguların demografik özellikleri ve tedavi bilgileri hasta dosyalarından edinildi. Olguların y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Isotretinoin earliest clinical response usually is observed after 4-6 weeks of therapy (Agarwal, Besarwal, & Bhola, 2011;Izol, Başkan, Başar, Tunali, & Saricao glu, 2012). For the last three decades, it has been observed through animal model studies that isotretinoin therapy can alter several functions of innate immunity during this period of a clinical trial, and many studies were performed, although with varying reported results for both animal models and human (Holland, Gallon, & Cunliffe, 1984;McKerrow, Mackie, Lesko, & Pearson, 1988).…”
Section: Antimicrobial Peptides Play a Dual Role In Acne Vulgaris Thmentioning
confidence: 99%
“…Isotretinoin earliest clinical response usually is observed after 4-6 weeks of therapy (Agarwal, Besarwal, & Bhola, 2011;Izol, Başkan, Başar, Tunali, & Saricao glu, 2012). For the last three decades, it has been observed through animal model studies that isotretinoin therapy can alter several functions of innate immunity during this period of a clinical trial, and many studies were performed, although with varying reported results for both animal models and human (Holland, Gallon, & Cunliffe, 1984;McKerrow, Mackie, Lesko, & Pearson, 1988).…”
Section: Antimicrobial Peptides Play a Dual Role In Acne Vulgaris Thmentioning
confidence: 99%